Use of Gamma Irradiation for Control of Postharvest Botrytis cinerea Bunch Rot of Table Grapes in Cold Storage - de Kock, P.J.; Holz, G. (South African Journal of Enology and Viticulture, 2017)
The feasibility of employing gamma irradiation for the control of postharvest Botrytis bunch rot of table grapes in cold storage was studied. Table grape cultivars from commercial vineyards in the Paarl and Hex River Valley areas were packed as for export in vented corrugated cartons. The cartons were irradiated at O; 1,5; 2,0 or 3,0 kGy. After irradiation, grapes were kept for 4 weeks at -0,5°C, followed by another week at 10°C. Less decay was observed when table grapes were irradiated soon after packing than after a storage period. Irradiation at 1,5; 2,0 and 3,0 kGy reduced the effect of Botrytis cinerea on Barlinka grapes stored without sulphur dioxide. Irradiation of Waltham Cross and Barlinka grapes at a dose of 2,0 kGy, combined with reduced S02 treatments, resulted in similar control as with the standard practice of enclosing an S02 generator. Browning of Waltham Cross berries and bacterial and yeast growth occurred on the surface of berries irradiated at a dose of 3,0 kGy. Irradiation had no adverse effect on other aspects of quality.